ANALISIS POSITIONING RESTORAN CEPAT SAJI WARALABA FRIED CHICKEN DI BANJARMASIN BERDASARKAN PERSEPSI KONSUMEN (Studi Pada KFC Duta Mall, Texas Fried Chicken Duta Mall, AW Duta Mall Dan California Fried Chicken Rs Ulin Banjarmasin) - Prihatini Ade Mayvita; Ikhwan Faisal (JWM (JURNAL WAWASAN MANAJEMEN), 2015)
During the last 14 years, the growth rate of fried chicken franchise with the concept of fast food restaurants in Banjarmasin is 12% per year. It is characterized by large number of outlets/stores of fried chicken franchise in Banjarmasin city as many as 10 outlets. Most of the existing outlets are in Duta Mall Banjarmasin. This study aims to identify and analyze the competitive position of fried-chicken fast-food franchise restaurants based on the consumers’ perceptions (Study on KFC, Texas Fried Chicken, AW Duta Mall and CFC RS Ulin Banjarmasin). Perceptions formulated are based on the assessment of marketing mix, which consists of services, physical condition, Product, promotion, personal traits, Price, means of support, distribution and location. 100 respondents are taken as samples in this study, i.e. respondents who have eaten in the fourth Fried Chicken fast food franchise using the technique of non proportional stratified random sampling. Meanwhile, the technique of data analysis uses Multi Dimensional Scaling (MDS). The findings from the analysis using Multi Dimensional Scaling (MDS) show inequality positions of Fried Chicken franchise restaurants, Kentucky Fried Chicken, Texas Chicken, AW and California Fried Chicken, based on their consumers’ perceptions: 1. KFC is a fried chicken franchise restaurant that has superiority over the ease in getting information for organizing parties, the rooms’ capacities, the frequency of advertisements, employee skills, appropriate Products with Prices. In addition, KFC also has special superiority over different/ unique fried chicken taste and more outlets than other fried chicken franchise restaurants; 2. Texas Fried chicken has superiority over the speed of Customer service, cleanliness of the room, the Product pakaging which is favorable to consumers, direct gifts, discounts for the purchases, hospitable employees in serving customers, appropriate places for washing hands in accordance with the expectations of consumers of being close to additional facilities; 3. Customers perceive AW has superiority over the ease of organizing parties and designing more interesting party rooms, standard Product size, cheaper unit prize of Products, more varied promotion media, and neatness of employees’ clothes. In addition, AW also has a special superiority with the availability of quite complete and spacious children’s playground, 4. California Fried chicken (CFC) has superiority over the accuracy in giving services, attractive room design, more varied menu selection, cheaper package Prices, and comfortable atmosphere.